Answer:
f(-2) = -1
Step-by-step explanation:
One way of doing this is to substitute -2 for x in every place where x shows up:
f(x) = 4x + 3x^2 − 5 → f(-2) = 4(-2) + 3(-2)^2 − 5
→ f(-2) = -8 + 3(4) - 5, or f(-2) = 4 - 5, or f(-2) = -1
Mai's penny bank can hold 498 pennies without being full.
Answer:
Step-by-step explanation:
The x-y coordinates for the given equation are: (-2,11),(-1,7),(0,3), (1,-1) and (2,-5).
<h3>Linear Function</h3>
A linear function can be represented by a line. The standard form for this equation is: ax+b , for example, y=2x+7. Where:
- a= the slope;
- b=the constant term that represents the y-intercept.
The given equation is 16x + 4y = 12. For solving this question, you should replace the given values of x for finding the values of y.
Thus,
- For x= -2, the value of y will be:
16*(-2)+4y=12
-32+4y=12
4y=12+32
4y=44
y=11
- For x= -1, the value of y will be:
16*(-1)+4y=12
- -16+4y=12
- 4y=12+16
- 4y=28
- y=7
- For x= 0, the value of y will be:
16*(0)+4y=12
- For x= 1, the value of y will be:
16*(1)+4y=12
- 16+4y=12
- 4y=12-16
- 4y=-4
- y= -1
- For x= 2, the value of y will be:
16*(2)+4y=12
- 32+4y=12
- 4y=12-32
- 4y=-20
- y= -5
Read more about the linear equation here:
brainly.com/question/1884491
#SPJ1